2021
DOI: 10.1136/bmjopen-2020-043926
|View full text |Cite
|
Sign up to set email alerts
|

Training general practitioners in melanoma diagnosis: a scoping review of the literature

Abstract: BackgroundGeneral practitioners (GPs) play a key role in early melanoma detection. To help GPs deal with suspicious skin lesions, melanoma diagnostic training programmes have been developed. However, it is unclear whether these programmes guarantee the acquisition of skills that will be applied by GPs in their daily clinical practice and maintained over time.ObjectivesThis scoping review aimed to examine and compare educational programmes designed to train GPs in melanoma diagnosis using clinical (naked eye) e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 68 publications
1
16
0
Order By: Relevance
“…In particular participants thought dermoscopy training needed to be hands-on, practical, and that short one-off training was inadequate. This concurs with the results of a scoping review looking at programs to train GPs in melanoma diagnosis, which found that the programs that led to sustained improvement in GPs’ clinical practice included refresher training material [ 42 ]; moreover the effectiveness of ongoing dermoscopy training for GPs delivered via distance learning has shown promising potential. [ 43 ] Conversely, a questionnaire study carried out among GPs with an interest in dermatology found that the majority reported feeling confident using dermoscopy after short-term training [ 27 ].…”
Section: Discussionsupporting
confidence: 75%
“…In particular participants thought dermoscopy training needed to be hands-on, practical, and that short one-off training was inadequate. This concurs with the results of a scoping review looking at programs to train GPs in melanoma diagnosis, which found that the programs that led to sustained improvement in GPs’ clinical practice included refresher training material [ 42 ]; moreover the effectiveness of ongoing dermoscopy training for GPs delivered via distance learning has shown promising potential. [ 43 ] Conversely, a questionnaire study carried out among GPs with an interest in dermatology found that the majority reported feeling confident using dermoscopy after short-term training [ 27 ].…”
Section: Discussionsupporting
confidence: 75%
“…A recent scoping review of the literature published in 2021 also suggests that training modality does not influence the overall acquired performance of GPs while longer-term sustainability of performance is achieved with programmes that provide refresher training material. 26 While ensuring ongoing education and upskilling are important steps when implementing models of shared care, support for GPs should also be taken into consideration and this could be in the form of rapid access to dermatology referral pathways as indicated by study respondents. At present, triage criteria and pathways are already in place at tertiary centres in South Australia.…”
Section: Discussionmentioning
confidence: 99%
“…In line with this, providing post-graduate skin cancer education to GPs has demonstrated to improve the diagnostic accuracy of primary care physicians [ 25 27 ]. However, post-graduate training of GPs typically involves dermatologists to provide education, which can be labor-intensive and costly, and refresher material seems critical to maintaining acquired skills [ 28 ]. AI may be a useful complementary educational tool in addition to human teaching, which may prove helpful to scale post-graduate education of GPs and can be used according to their individual needs.…”
Section: Discussionmentioning
confidence: 99%